An Army Marches on Its Stomach: Metabolic Intermediates as Antimicrobial Mediators in Mycobacterium tuberculosis Infection - Hackett, Emer E.; Sheedy, Frederick J. (Frontiers in Cellular and Infection Microbiology, 2020)
The cells of the immune system are reliant on their metabolic state to launch effective responses to combat mycobacterial infections. The bioenergetic profile of the cell determines the molecular fuels and metabolites available to the host, as well as to the bacterial invader. How cells utilize the nutrients in their microenvironment -including glucose, lipids and amino acids -to sustain their functions and produce antimicrobial metabolites, and how mycobacteria exploit this to evade the immune system is of great interest. Changes in flux through metabolic pathways alters the intermediate metabolites present. These intermediates are beginning to be recognized as key modulators of immune signaling as well as direct antimicrobial effectors, and their impact on tuberculosis infection is becoming apparent. A better understanding of how metabolism impacts immunity to Mycobacterium tuberculosis and how it is regulated and thus can be manipulated will open the potential for novel therapeutic interventions and vaccination strategies.